2014
DOI: 10.3389/fneur.2014.00005
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury and Olfaction: A Systematic Review

Abstract: Traumatic brain injury (TBI) is a common condition that is often complicated by neuropsychiatric sequelae that can have major impacts on function and quality of life. An alteration in the sense of smell is recognized as a relatively common complication of TBI; however in clinical practice, this complication may not be sought or adequately characterized. We conducted a systematic review of studies concerned with olfactory functioning following TBI. Our predetermined criteria led to the identification of 25 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
111
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(124 citation statements)
references
References 25 publications
3
111
0
10
Order By: Relevance
“…In a recent systematic review, authors found that hyposmia (reduced olfactory function) was present in 20-40% of mild traumatic brain injury (TBI) patients [42]. From those mild TBI patients who experience hyposmia, $10% recover naturally from post-traumatic olfactory loss [44].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a recent systematic review, authors found that hyposmia (reduced olfactory function) was present in 20-40% of mild traumatic brain injury (TBI) patients [42]. From those mild TBI patients who experience hyposmia, $10% recover naturally from post-traumatic olfactory loss [44].…”
Section: Introductionmentioning
confidence: 98%
“…The olfactory system stands out as a relevant study target to investigate the mediating effects of the BDNF val66met polymorphism on long-term brain sequelae after concussion considering that (1) olfactory dysfunction is highly prevalent after concussive injury and its presence can serve as a potential marker of additional structural or functional morbidities [42]; (2) the olfactory bulb is among a few brain structures that has the ability to regenerate itself through BNDF-dependent brain plasticity and neurogenesis processes [43]; and (3) BDNF plays a central role in olfactory function [43]. In a recent systematic review, authors found that hyposmia (reduced olfactory function) was present in 20-40% of mild traumatic brain injury (TBI) patients [42].…”
Section: Introductionmentioning
confidence: 99%
“…Still, other studies reported that frontal lesions were associated with worse performance on olfactory tests 65 .…”
Section: Traumatic Head Injury and Olfactionmentioning
confidence: 97%
“…Nowadays, it is well known, though even minor THI could determine anosmia 64 . Within the reviewed clinical studies, the reported prevalence of patients with olfactory complaints among cases with "mild" THI was between 20% -44%; among those with "moderate" THI: 37% -68.4%; with "moderate to severe" THI: 49% -56%; and with severe THI: 33% -61% 65 .…”
Section: Traumatic Head Injury and Olfactionmentioning
confidence: 99%
See 1 more Smart Citation